2002
DOI: 10.1111/1469-8986.3960767
|View full text |Cite
|
Sign up to set email alerts
|

Auditory memory for backward masking signals in children with language impairment

Abstract: This study was designed to investigate early auditory memory and its possible contribution to an auditory processing deficit shown by some children with language impairment. Ten children with language impairment and 10 age-matched controls participated in a series of simultaneous and backward masking tasks. The same backward masking stimulus was then used to elicit a mismatch negativity response. In the behavioral conditions, children in the language impairment group had significantly higher (poorer) signal th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 83 publications
2
26
0
Order By: Relevance
“…The backward masking findings reported here reinforce previous research, linking children with LPs with poor backward masking thresholds (Marler, Champlin, & Gillam, 2002;Wright et al, 1997).…”
Section: Relationships Between Backward Masking and Speech Perceptionsupporting
confidence: 91%
See 2 more Smart Citations
“…The backward masking findings reported here reinforce previous research, linking children with LPs with poor backward masking thresholds (Marler, Champlin, & Gillam, 2002;Wright et al, 1997).…”
Section: Relationships Between Backward Masking and Speech Perceptionsupporting
confidence: 91%
“…Kujala et al suggested that backward masking interferes with sound perception at the level of the cortex at a preattentive level. Marler et al (2002) showed MMN latency delays and amplitude decreases in children with high backward masking thresholds. Additionally, they saw correlations between MMN and behavioral memory, and suggested impaired early memory mechanisms for complex sounds (Marler et al, 2002).…”
Section: Cortical Consequencesmentioning
confidence: 92%
See 1 more Smart Citation
“…These developmental trends are consistent with data from other investigations in which multiple masking conditions, sim- ilar to the present ones, were tested. Compared with same-age controls, thresholds were significantly higher (effect sizes are not available) in the backward but not the onset condition for Ϸ9.3-year-old children with specific language impairment (31) and in the backward but not the forward or delay conditions for Ϸ13-year-old children with dyslexia (29). Additionally, thresholds for a briefer tone than was used here tended to decrease with increasing age in backward, forward, and delay conditions in controls between 5 and 11 years old (32).…”
Section: Resultsmentioning
confidence: 97%
“…However, results from several studies are consistent with the suggestion that attention to speech and/or auditory information may differ between SLI and TLD groups. Specifically, several studies have found later latency of N1 in, at least, a subset of Language Impaired (LI) children (Jirsa & Clontz, 1990;Neville, et al, 1993;Tonnquist-Uhlen, Borg, Persson & Spens, 1996), although this was not seen in other studies (e.g., Lincoln, et al, 1995;Marler, Champlin & Gillam, 2002). These differences in N1 latency could be due to reduced N1 negativity leading to the appearance of later N1 peak latency.…”
Section: Introductionmentioning
confidence: 96%